A Novel and Likely Inherited Lymphoproliferative Disease in British Shorthair Kittens. (November 2015) - Aberdein, D.; Munday, J. S.; Fairley, R. A.; Vernau, W.; Thompson, K. G.
An unusual lymphoproliferative disease was identified in multiple closely related British Shorthair (BSH) kittens, suggesting an inherited predisposition to disease. Affected kittens typically developed rapidly progressive and marked generalized lymphadenopathy, moderate splenomegaly, and regenerative and likely hemolytic anemia from 6 weeks of age. Microscopic findings were suggestive of multicentric T-cell lymphoma, but additional testing revealed a polyclonal population of CD3+/CD4–/CD8– "double negative" T cells (DNT cells). This is a novel disease presentation with similarities to the human disorder autoimmune lymphoproliferative syndrome (ALPS), a rare inherited disease causing lymphoproliferation and variable manifestations of autoimmunity. The human disease is most commonly due to the presence of Fas gene mutations causing defective lymphocyte apoptosis, and further investigations of both the mode of inheritance and genetic basis for disease in affected cats are currently in progress.